Early rehabilitation in patients with acute aneurysmal subarachnoid hemorrhage. (July 2015) - Karic, Tanja; Sorteberg, Angelika; Haug Nordenmark, Tonje; Becker, Frank; Roe, Cecilie
Abstract Purpose: The aim of this study was to describe and quantify the content of early rehabilitation adapted to patients with acute aneurysmal subarachnoid hemorrhage (aSAH) and to assess its feasibility. Methods: This was a prospective, observational study including 37 aSAH patients. Early rehabilitation was applied according to a mobilization algorithm. Clinical parameters, the time that rehabilitation team used on early rehabilitation and progression in mobilization were recorded. The patients' clinical conditions were graded according to the World Federation of Neurological Surgeons scale (WFNS). Results: Poor-grade patients (WFNS 3, 4, 5) (n = 12) received more rehabilitation (median 412 min) than did good-grade patients (WFNS 1, 2) (median 240 min). Mobilization to 60° of head elevation in good-grade patients began on day one after securing the aneurysm. Out-of-bed mobilization was possible on day three. Poor-grade patients were mobilized to 60° after two days and were out of bed on day seven. At discharge, 67% of poor-grade patients were mobilized to walking versus 78% of good-grade patients. No serious adverse effects to early rehabilitation were observed. Conclusions: Early rehabilitation in aSAH patients is feasible from the first day after securing the aneurysm. The rehabilitation content varied according to the patient's clinical grade. Implications for Rehabilitation Early rehabilitation is feasible from the first day after securing the ruptured aneurysm in patients with aneurysmal subarachnoid hemorrhage (aSAH). Early rehabilitation requires close monitoring and continuous adjustment for the content and amount according to the patient's clinical condition. Interdisciplinary collaboration is recommended to match the rehabilitation needs to the medical condition on a daily basis.